High seroprevalence of Rift Valley fever phlebovirus in domestic ruminants and African Buffaloes in Mozambique shows need for intensified surveillance. Issue 1 (1st January 2017) - Moiane, Belisário; Mapaco, Lourenço; Thompson, Peter; Berg, Mikael; Albihn, Ann; Fafetine, José
ABSTRACT: Introduction : Rift Valley fever (RVF) is an arthropod-borne disease that affects both animals and humans. RVF phlebovirus (RVFPV) is widespread in Africa and Arabian Peninsula. In Mozambique, outbreaks were reported in South; seroprevalence studies performed in livestock and water buffaloes were limited to central and south regions. We evaluated the seroprevalence of RVFPV among domestic ruminants and African buffaloes from 7 of 10 provinces of Mozambique, to understand the distribution of RVFPV and provide data for further RVF control programs. Materials and methods : A total of 1581 blood samples were collected in cattle, 1117 in goats, 85 in sheep and 69 in African buffaloes, between 2013 and 2014, and the obtained sera were analyzed by ELISA. Results and discussion : The overall seroprevalence of RVFPV domestic ruminants and African buffaloes was 25.6%. The highest was observed in cattle (37.3%) and African buffaloes (30.4%), which were higher than in previous studies within Mozambique. In south and central regions, the overall seroprevalences were higher (14.9%–62.4%) than in the north. Conclusion : This study showed the presence of anti-RVFPV antibodies in animals from all sampled provinces, suggesting that RVFPV is actively circulating among domestic ruminants and African buffaloes in Mozambique, therefore surveillance should be intensified.